Nieszpory – śpiewana modlitwa Kościoła - Wiśniewski, Piotr (Teologia i Człowiek, 2014)
The liturgy of the Catholic Church does not confine itself only to celebrating the Eucharist and other sacraments. One of the forms of the liturgy after the Second Vatican Council are vespers. The Church documents indicate clearly that at least on Sundays and greater holidays, vespers should be celebrated with the faithful. The roots of this prayer can be found in the Old Testament and in the example set by Jesus. The golden age of the development of vespers falls on the 4th and 5th centuries. It was the time of creation of the obligation and the structure of the liturgical prayer of the Church. An integral part of each solemn liturgy, also vespers celebrated with a community, is music. Singing is an indispensable element of common prayer and it reflects best the character of the public Christian worship. This study concentrates especially on singing psalms, hymns and responsories, not excluding the possibility of singing also other parts of this service (antiphones, readings from the Bible, the Our Father). First of all, it was shown that due to its nature vespers should be sung. Psalms and hymns were created mainly to be sung and thanks to it “prayer gains special sacring”. Different forms of celebrating vespers, such as individual, with a community of the faithful and connected to the Mass, were pointed to. Celebration of vespers with the community is still a great challenge to the Church after the Second Vatican Council. Undoubtedly, there is a need for dynamic popularization and appreciation of vespers, first, by the very priests in order not to limit Sunday prayer only to celebrating the Eucharist.